The Economics of the Asset Depreciation Range System: The Case Against ADR - Taubman, Paul (Journal of Finance, 1972)
Paul Taubman, The Economics of the Asset Depreciation Range System: The Case Against ADR, The Journal of Finance, Vol. 27, No. 2, Papers and Proceedings of the Thirtieth Annual Meeting of the American Finance Association, New Orleans, Louisiana, December 27-29, 1971 (May, 1972), pp. 511-524